Strabismus Surgery for Abnormal Head Position: 7-Year Experience at a Tertiary Care Center - Santos Oliveira, Joana (2022)
INTRODUCTION: Traditionally, the goal of strabismus treatment has been to realign the visual axes in order to eliminate diplopia, to produce, maintain, or restore binocular vision or for aesthetic reasons. Nowadays, surgery to improve an abnormal head position (AHP) is also a well-accepted indication for surgery. AHP or torticollis is a frequent encountered sign in routine ophthalmology practice, especially in pediatric patients. The present study aims to characterize the patients of a tertiary hospital who were submitted to surgery for an AHP caused by an ocular condition, as well as the results obtained by the treatment provided to them. MATERIAL ANd METHODS: The medical records of patients who were admitted to surgery for an AHP in the Ophthalmology department of Centro Hospitalar Universitário de São João between July 2014 and July 2021 were retrospectively studied. The patients underwent ophthalmologic examinations pre and post-operatively. Characterization of the AHP was subjectively evaluated. RESULTS: In total, 24 patients were studied, 8 (33.3%) of whom were female and 16 (66.6%) were male. Mean age of patients was 13.7 years (range 3-61 years). There were 7 patients with superior oblique palsy, 7 patients with Duane syndrome (type 1), 6 patients with nystagmus, 3 patients with third nerve paralysis and 1 patient with Brown syndrome. Face turn was the most frequent AHP (14 patients), followed by head tilt AHP (5 patients). Four patients had mixed AHP (head tilt and face turn) and 1 patient presented with chin up. A total of 95.8% of patients had their AHP improved with surgical treatment. Nineteen patients were submitted to one surgery and a second surgery was necessary in 5 patients. CONCLUSION: Overall, almost all patients improved after surgery. Nevertheless, it is important to highlight that occasionally it is necessary more than one surgery to achieve the best result,